The Role Of Testimonials And Online Reviews In Influencing Purchase Decisions With Customer Engagement As A Mediating Variable (A Study on Consumers of PT. Java Abadi Gemilang) - Pangestu, Adzi; Brabo, Nora Andira (Jurnal Multidisiplin Sahombu, 2025)
This study examines the role of testimonials and online customer reviews in influencing consumer purchase decisions, with customer engagement as a mediating variable. The research was conducted on consumers of PT. Java Abadi Gemilang, an IT services company. Using a quantitative explanatory approach, data were collected through a questionnaire distributed to 97 respondents selected using purposive sampling. The research instrument employed a five-point Likert scale and was tested for validity and reliability using SPSS and SmartPLS. Data analysis was conducted using the Partial Least Square (PLS) method to evaluate both the measurement model (outer model) and the structural model (inner model). The results show that online reviews significantly influence both customer engagement and purchase decisions, while testimonials do not. Moreover, customer engagement significantly mediates the relationship between online reviews and purchase decisions. These findings highlight the importance of interactive digital strategies in consumer behavior.